The Mixed Fermentation Technology of Solid Wastes of Agricultural Biomass - Zhang, Feng; Yu, Wei; Liu, Wenhe; Xu, Zhanyang (Frontiers in Energy Research, 2020)
Due to the large quantity and wide range of solid wastes of the biomass, and the dual characteristics of pollution and resource utilization, the energy utilization of anaerobic fermentation can promote its pollution control, so the mixed fermentation technology of solid wastes of agricultural biomass was studied. Corn straw, pig manure, and kitchen waste were selected as solid wastes of agricultural biomass. A system including a temperature control device, a fermentation device and a gas gathering device is used to measure the content and pH value of biogas and methane. Physical, chemical, and biological pretreatment methods were used to strengthen the anaerobic reference of biomass, and the mixed fermentation of different biomass was used to complete the anaerobic fermentation of a variety of solid wastes of agricultural biomass. The results showed that pig manure and corn straw were suitable for medium temperature fermentation at 30°C, while cow manure and corn straw were suitable for high temperature fermentation at 60°C. In the process of anaerobic fertilization, when the ratio of cow dung to sludge is 2:1, 3:1, and 4:1 respectively, the methane content is shown as follows: (1) The first 130 days are relatively stable and then slowly decreased; (2) The first 120 days are slowly increased, and then it rises to the maximum value at 140 days and then remains unchanged; (3) It remains at 2% all the time. After the mixture of cow manure and sludge, the higher the proportion of cow manure is, the higher the pH value in the initial stage of anaerobic fertilization is. The higher the basicity of methanogens in the fermentation liquid inside the fermentation tank is, the higher the pH value of the system is, and the basicity of methanogens has a significant positive correlation with the crude protein content of biomass.